Case Report: Utility of Ketamine, Lidocaine, and Mexiletine as Nonopioid Adjuvants in Complex Cancer-Associated Pain. (2nd January 2018) - Hakim, Robert C.; Edmonds, Kyle P.; Atayee, Rabia S.
ABSTRACT: Ketamine, lidocaine, and mexiletine are potential nonopioid adjuvant medications for the use of refractory cancer-related pain, particularly when opioids are demonstrating limited objective benefit. This is a case report of a single patient admitted to a large academic medical center in the United States. The patient is a 43-year-old woman with a history of Crohn's disease complicated by rectal squamous cell carcinoma and complex, progressive, and intractable pelvic and rectal pain. Over the course of hospitalization, her pain demonstrated limited opioid responsiveness despite marked fluctuations of her oral morphine equivalent doses. She also demonstrates variable responsiveness to ketamine. Lidocaine continuous infusion ultimately proves beneficial, and she is discharged after conversion to oral mexiletine. An overview of the hospital system's protocols for ketamine and lidocaine continuous infusions for pain and considerations for transitioning to mexiletine from lidocaine infusion are included.